Moonlight on the magic flute ebook - Osborne, Mary Pope (Magic Tree House: Merlin Missions, 2009)
The #1 bestselling chapter book series of all time celebrates 25 years with new covers and a new, easy-to-use numbering system! Jack and Annie head to 18th-century Austria, where they must find and help a musician by the name of Mozart. Decked out in the craziest outfits they’ve ever worn—including a wig for Jack and a giant hoopskirt for Annie!—the two siblings search an entire palace to no avail. Their hunt is further hampered by the appearance of a mischievous little boy who is determined to follow them everywhere. But when the boy lets the animals out of the palace zoo, Jack and Annie have to use the only magic at their disposal to save themselves and the naughty little fellow. Formerly numbered as Magic Tree House #41, the title of this book is now Magic Tree House Merlin Mission #13:  Moonlight on the Magic Flute. Did you know that there’s a Magic Tree House book for every kid? Magic Tree House: Adventures with Jack and Annie, perfect for readers who are just beginning chapter books Merlin Missions: More challenging adventures for the experienced reader Super Edition: A longer and more dangerous adventure Fact Trackers: Nonfiction companions to your favorite Magic Tree House adventures Have more fun with Jack and Annie at MagicTreeHouse.com!